Medical termination of unplanned pregnancies in women with diabetes - Bharti Kalra; Yashdeep Gupta; Nitin Kapoor; Sanjay Kalra (Journal of the Pakistan Medical Association, 2025)
Women living with diabetes may experience unplannedpregnancies. This poses challenges and risk to bothmaternal and foetal health in case glycaemia and otherassociated comorbidities are not optimized. This may leadto doubts regarding continuation of pregnancy, giventhere are no clear guidelines or position statement fordecision regarding termination or continuation ofpregnancy. Multiple biomedical, psychosocial andenvironmental factors determine the course andoutcome of such pregnancies. In such situations, acomprehensive analysis of foeto maternal health helpsinform the antenatal woman, so that the right decisioncan be made, in a person-centred manner. This reviewproposes various algorithms to assist in shared decisionmaking, including a 2x2x2 rubric (Psychosocial: statutory(legal), system-specific; emotional, economic; Biomedical:obstetric, offspring health; medical, metabolic health). Nosingle biochemical value should be taken as an indicationfor termination of pregnancy, unless the foetus isincompatible with life. Keywords: Congenital malformations, diabetes, medicaltermination of pregnancy, obstetric health, pregnancy